Il problema della realtà nella metapsicologia freudiana - Baldini, Franco (Metapsychologica - rivista di psicanalisi freudiana, 2024)
The problem of external reality in Freudian metapsychology. Through an in-depth analysis of Freudian texts on the subject, this article highlights the metapsychological dimension of the concept of external reality and its importance for a clear structural description of psychoanalytic nosography. It also demonstrates its relevance in addressing several unresolved issues in Saussurianderived linguistics. Additionally, the argument underscores the inconsistency of Lacan’s interpretation of the same texts.